Intra-racism in Hansberry’s A Raisin in the Sun: A Sociological Study - Hama, Bakhtiar S. (Sulaimani Journal for Humanities, 2019)
This paper studies intra-racism in A Raisin in the Sun, a play by the African-American playwright Lorraine Hansberry. Intra-racism or internalized racism is a term used to talk about the violence which is performed among the members of the same group who are themselves oppressed by others or another group. Hansberry focuses on the life of a black family which consists of five members who are victims of both racism and intra-racism. Sense of inferiority increases the tensions among The Walters, and each one tries to escape it in their own way; Ruth and Mama by having a house, Walter by going into business and opening a liquor store and Beneatha by becoming a doctor. The researcher studies the relationship between the characters and how they face each other when engaged in conversations. The aim of the paper is to show how people of colour become oppressors in their own communities and to achieve the aims of the research, the tenets of critical social theory are applied, and especially what is related to gender, power and oppression.
Keywords: racism; intraracism; inferiority; gender; sociological criticism